BIOPHYSICAL AND MEDICAL ROLES OF FIREFLIES - Uzokova Shakhzoda Sobir kizi (Journal Park Publishing, 2022)
Bioluminescence reactions are widely used in in vivo optical imaging in the field of natural sciences and medicine. Such reactions produce light upon oxidation of luciferin (substrate) catalyzed by luciferase (enzyme), and this bioluminescence makes it possible to quantify tumor cells and gene expression in animal models. Many researchers have developed single-color or multi-color bioluminescent systems based on artificial analogues of luciferin and/or luciferase mutants for use in bioluminescent imaging in vivo.
Keywords: luciferin; luciferase; oxygen